Maternal near-miss due to unsafe abortion and associated short-term health and socio-economic consequences in Nigeria (2015)
Little is known about maternal near-miss (MNM) due to unsafe abortion in Nigeria. We used the WHO criteria to identify near-miss events and the proportion due to unsafe abortion among women of childbearing age in eight large secondary and tertiary hospitals across the six geo-political zones. We also explored the characteristics of women with these events, delays in seeking care and the short-term socioeconomic and health impacts on women and their families. Between July 2011 and January 2012, 137 MNM cases were identified of which 13 or 9.5% were due to unsafe abortions. Severe bleeding, pain and fever were the most common immediate abortion complications. On average, treatment of MNM due to abortion costs six times more than induced abortion procedures. Unsafe abortion and delays in care seeking are important contributors to MNM. Programs to prevent unsafe abortion and delays in seeking postabortion care are urgently needed to reduce abortion related MNM in Nigeria.